Alcohol Expectancies Mediate the Relationship Between Age of First Intoxication and Drinking Outcomes in College Binge Drinkers. (15th April 2016) - Stamates, Amy L.; Lau-Barraco, Cathy; Linden-Carmichael, Ashley N.
ABSTRACT: Background : While prior research has shown that age of first intoxication (AI) is associated with negative alcohol outcomes, limited research has examined factors accounting for this relationship. Alcohol expectancies, or beliefs about the effects of alcohol, may explain such associations as both positive and negative expectancies have been shown to be key predictors of drinking outcomes. Objective : The present study examined expectancies as mediators between early AI and alcohol-related outcomes. Method : Data collection occurred in 2012 and 2013. Participants were college students ( N = 562, 65.8% women) who completed an online survey including measures of alcohol use history, alcohol expectancies, typical alcohol consumption, and alcohol-related problems. Structural equation modeling was used to test the hypothesized model. Results : Our findings support a model whereby AI is associated with drinking through its influence on both positive and negative expectancies. Specifically, an earlier AI was associated with stronger alcohol expectancies, which in turn, was associated with heavier alcohol use and alcohol-related problems. Conclusions/Importance : These findings are consistent with expectancy theory and previous research suggesting that more experienced drinkers hold stronger drinking-related beliefs, be it positive or negative, and these expectancies ultimately explain variability in alcohol use and problems. Our findings further support that expectancies play an important role in the initiation of drinking behavior.